O1-S03.02 Cephalosporin susceptibility of Neisseria gonorrhoeae isolates in the USA, 2000–2010. (10th July 2011) - Kirkcaldy, R; Murray, E; Del Rio, C; Hall, G; Hook, E; Whittington, W; Papp, J; Weinstock, H
Abstract : Background: Cephalosporins are recommended by CDC for first-line gonorrhoea treatment. Declining cephalosporin susceptibility and clinical cefixime treatment failure have been reported from Asia, Europe and other regions. We report cephalosporin susceptibility trends among US N gonorrhoeae isolates. Methods: The Gonococcal Isolate Surveillance Project (GISP) is a sentinel surveillance system that monitors antimicrobial susceptibility among isolates collected from men with urethritis. Minimum inhibitory concentrations (MICs) are determined by agar dilution. The proportion of isolates with elevated MICs to cefixime (≥0.25 μg/ml) and ceftriaxone (≥0.125 μg/ml) from 2000 through the first half of 2010 were tested for trends using the Cochran-Armitage trend test. Susceptibility tests for cefixime were not performed during 2007–2008. Results: 61 559 isolates were tested during 2000–June 2010 (annual mean=5845). Overall, 37% of isolates were from men in the northeastern or southern regions of the US, 25% were from the Midwest, and 38% were from the West; 21% were from men who have sex with men (MSM). The proportion of isolates with elevated MICs remained stable for cefixime (CFX) from 2000 to 2006 (0.2% to 0.1%; CFX susceptibility not tested 2007 and 2008) and for ceftriaxone (CRO) from 2000 to 2008 (0.1% to 0.1%); the proportions increased in 2009 and 2010 (CFX: 0.8% and 1.9% [n=53], p<0.001; CRO: 0.3% and 0.4% [n=11], p<0.001). In 2010, most isolates with elevated MICs to cephalosporins were from the West (CFX: n=48 [91%]; CRO: n=7 [64%]) and from MSM (CFX: n=46 [87%]; CRO; n=9 [82%]). Conclusions: The proportion of gonococcal isolates with elevated MICs to cefixime and ceftriaxone recently increased in the US. Most of the isolates with elevated MICs were from men in the West and MSM. This is worrisome given trends elsewhere in the world and the history of fluoroquinolone-resistance in the US, which, early in the epidemic, was most often detected in the western US and among MSM. Cephalosporins remain effective for gonorrhoea treatment in the US, yet increasing MICs suggest that resistance may emerge. If cephalosporin resistance does emerge, alternative antibiotic treatment options will be needed.